2023
DOI: 10.7759/cureus.41914
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approaches and Therapies to Enhance Neuroplasticity and Promote Recovery in Patients with Neurological Disorders: A Narrative Review

Jitesh Kumar,
Tirath Patel,
Fnu Sugandh
et al.

Abstract: Brain rehabilitation and recovery for people with neurological disorders, such as stroke, traumatic brain injury (TBI), and neurodegenerative diseases, depend mainly on neuroplasticity, the brain's capacity to restructure and adapt. This literature review aims to look into cutting-edge methods and treatments that support neuroplasticity and recovery in these groups. A thorough search of electronic databases revealed a wide range of research and papers investigating several neuroplasticity-targeting methods, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…After brain damage, other regions scan, adapt, and take over functions from the affected area, aiding in attention recovery. Understanding the mechanisms of neuroplasticity offers insights into how interventions can be designed to optimize attention [ 39 ]. Training programs, therapies, and lifestyle changes encouraging focused and sustained attention can harness neuroplasticity to enhance attentional abilities.…”
Section: Attention Optimization Theorymentioning
confidence: 99%
“…After brain damage, other regions scan, adapt, and take over functions from the affected area, aiding in attention recovery. Understanding the mechanisms of neuroplasticity offers insights into how interventions can be designed to optimize attention [ 39 ]. Training programs, therapies, and lifestyle changes encouraging focused and sustained attention can harness neuroplasticity to enhance attentional abilities.…”
Section: Attention Optimization Theorymentioning
confidence: 99%
“…Research and development of neurotechnologies continues to progress at a rapid rate ( 7 9 ) and it is likely that in the future we will see the further development and deployment of more sophisticated brain–computer interfaces (BCI) and robotic devices, advances in materials and technological methods, and the identification of new technologies that have the potential to help those with what used to be considered as irreversible neurological outcomes to regain their functional capacity and quality of life. In 2022, the prospective, open-label, non-randomized Brain Gate feasibility study, the largest and longest-running clinical trial of an implanted BCI, reported positive safety results in patients with quadriparesis from spinal cord injury, brainstem stroke, or motor neuron disease ( 10 ), paving the way for further clinical research.…”
Section: The Technology Revolution and Its Impact On Neurological Pra...mentioning
confidence: 99%
“…This therapy aims to reduce cognitive impairment and improve awareness of cognitive difficulties encountered in daily living, thus having a positive impact on the quality of life of MS patients [73]. The underlying mechanisms explaining these beneficial effects correlate with the enhancement of functional and structural neuroplasticity, dependent on the trained cognitive tasks [74]. In addition, cognitive rehabilitation may induce beneficial neurobiological changes in the hypothalamic-pituitaryadrenal axis, improving the regulation of serotonin precursors and neurogenesis via direct mechanisms and also as an indirect effect that occurs with the decrease in the stress and depression level [75].…”
Section: The Impact Of Medication and Cognitive Rehabilitation On Cog...mentioning
confidence: 99%